Biological attributes of Steindachnerina insculpta (Fernandez-Yepez, 1948) (Curimatidae) in two reservoirs of middle Paranapanema River, Brazil - Brandão, Heleno [UNESP] (2013)
The aim of the present study was to evaluate the biological attributes of Steindachnerina insculpta in two reservoirs of middle Paranapanema River. Fish were collected with gillnets every two months at four sites of the Salto Grande Reservoir and quarterly at five sites of the Chavantes Reservoir. After confirmation of the species, were obtained biometric data, standard length, total weight and sex. This information was used to assess the biological attributes (abundance, sex ratio, length-weight relationship, condition factor and size class distribution) for each area. In both reservoirs, the sex ratio of the total samples differed from 1:1 and growth was positive allometric. The condition factor and length varied between sites. The most representative size class at all sites was 9.1 to 10.5 cm. This study demonstrates that the biological attributes of populations of S. insculpta are modified along the areas of the two reservoirs, reflecting the ability to adjust the species.